Effects of a cell phone conversation on cognitive processing performances. - Kemker BE; Stierwalt JAG; LaPointe LL; Heald GR (Journal of the American Academy of Audiology, 2009)
Background: The ability to apportion cognitive resources to process multiple visual and auditory stimuli is essential for human communication in competing conditions. Purpose: The purpose of the current research was to examine the effects of a cell phone conversation on a battery of cognitive tests, using both timing (RT) and accuracy (N) as dependent measures. Research Design: A repeated measures ANOVA was conducted. Study Sample: Forty-two college-age (mean 22 yr) adult females with normal hearing and cognitive function participated in the study. Data Collection and Analysis: In one condition (quiet), a standardized cognitive assessment battery was administered to participants in a quiet room. In the (cell phone) condition, subjects were formulating and responding to specific questions about their travel experiences during administration of the same cognitive assessment battery. The computer automatically records subject performance. Post-hoc pairwise comparisons were conducted using the Bonferroni approach. The alpha level was set at .05 for all data analysis. This method of analysis was repeated for each of the dependent measures, RT, and N. Results: The results revealed a consistent, significant effect on reaction time between the two conditions. The same analysis was also conducted to examine the effect of participation in a cell phone discussion on accuracy. As with RT, results revealed a consistent, significant affect on A' between the two conditions. Conclusions: Our study supports the notion that there are differential effects of auditory distracters across cognitive spheres. For simple automatic type visual cognitive tasks, the effect is minimal. However, as visual tasks increase in difficulty, the effect of the auditory distraction is magnified, particularly when the task requires extensive division of language resources.